2022
DOI: 10.12688/f1000research.74576.1
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of yellow fever vaccine virus from breast feeding mothers to their infants: reporting of yellow fever virus (YFV) RNA detection in milk specimens

Abstract: Background: Because of yellow fever’s serious impact on health, vaccination is the principal strategy to control the disease. Administration of the yellow fever vaccine to breastfeeding women should be before they complete 9 months post-delivery, in order to prevent transmission of the yellow fever vaccine virus to their infants through breast feeding. This study aimed to confirm whether the excretion of yellow fever vaccine virus is in milk of vaccinated breastfeeding mothers and to confirm the probable trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…An effective live attenuated (17D strain) vaccine is available for YFV and elicits a durable, life-long adaptive immune response [ 159 ]. The vaccine has historically been contraindicated in pregnancy, breastfeeding mothers, and infants under six months of age, as YFV RNA has been detected in breastmilk following vaccination [ 163 ] and there have been several cases of vaccine-associated encephalitis in newborns of recently vaccinated mothers [ 110 , 164 , 165 ]. However, recent studies of pregnant women receiving YFV vaccination have demonstrated no increased risk of fetal adverse events, and thus vaccination should be considered in the setting of severe epidemics or unavoidable travel to high-risk areas given the risk of severe disease in unvaccinated populations [ 166 , 167 , 168 , 169 , 170 , 171 ].…”
Section: Prevention Of and Vaccination For Flavivirus Infectionsmentioning
confidence: 99%
“…An effective live attenuated (17D strain) vaccine is available for YFV and elicits a durable, life-long adaptive immune response [ 159 ]. The vaccine has historically been contraindicated in pregnancy, breastfeeding mothers, and infants under six months of age, as YFV RNA has been detected in breastmilk following vaccination [ 163 ] and there have been several cases of vaccine-associated encephalitis in newborns of recently vaccinated mothers [ 110 , 164 , 165 ]. However, recent studies of pregnant women receiving YFV vaccination have demonstrated no increased risk of fetal adverse events, and thus vaccination should be considered in the setting of severe epidemics or unavoidable travel to high-risk areas given the risk of severe disease in unvaccinated populations [ 166 , 167 , 168 , 169 , 170 , 171 ].…”
Section: Prevention Of and Vaccination For Flavivirus Infectionsmentioning
confidence: 99%